Catheter ablation for supraventricular tachycardias: contemporary issues. (July 2013) - Giedrimas, Evaldas; Goldberger, Jeffrey J
The treatment of cardiac arrhythmias has evolved significantly over the last 30 years. Understanding of arrhythmia mechanisms has led to pharmacologic therapies, surgical interventions and the widely used percutaneous catheter ablation techniques. The focus of this review is centered on the current catheter ablation therapies available for supraventricular tachycardia. We will discuss current management strategies including challenges when considering catheter ablation therapy for management of supraventricular tachycardias: atrioventricular nodal reentrant tachycardia, atrioventricular reentrant tachycardia utilizing an accessory pathway, atrial tachycardia and atrial flutter. Selected contemporary issues related to supraventricular tachycardia physiology, ablation approaches and ablation outcomes and complications will be discussed. Future goals for electrophysiologists are to continue to improve procedural safety and efficiency, while maintaining the impressive success rates that have been achieved.